2022
DOI: 10.1029/2022gl098048
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Precipitation Produced by Relatively Weak Convective Systems in the Tropics and Subtropics

Abstract: This study investigates warm‐season extreme precipitation events (EPEs) with the focus on the less‐attended weak convection (WeEPEs) using spaceborne radar observations. WeEPEs are compared to EPEs with intense convection (InEPEs), including their frequency/location, convective structures, and storm environments. WeEPEs and InEPEs both account for about 30% of the EPEs, highlighting the importance of WeEPEs. Overland WeEPEs mainly occur over key monsoon regions and maximize over windward sides of coastal mount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
2
7
1
Order By: Relevance
“…RCs with mode of TB 10.4 at 230-265 K. Despite the low cloud top, these RCs contributed around 39.8% of the total rainfall amount. This result supported that many extreme precipitation events are produced by relatively weak convective systems (Xu et al, 2022). RCs with mode of TB 10.4 at 230-265 K were related to the quasi-stationary front over south China; therefore, they were distributed near the average location of front at 23 -27 N. The mid-level pressure gradient over the study region and westerly winds were significantly stronger than the other two classes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…RCs with mode of TB 10.4 at 230-265 K. Despite the low cloud top, these RCs contributed around 39.8% of the total rainfall amount. This result supported that many extreme precipitation events are produced by relatively weak convective systems (Xu et al, 2022). RCs with mode of TB 10.4 at 230-265 K were related to the quasi-stationary front over south China; therefore, they were distributed near the average location of front at 23 -27 N. The mid-level pressure gradient over the study region and westerly winds were significantly stronger than the other two classes.…”
Section: Discussionsupporting
confidence: 73%
“…However, the average dBN w of convective precipitation for RCs with mode of TB 10.4 < 230 K (~32.2) was significantly lower than extreme precipitations (~39.8), showing that there was more prominent coalescence warm‐rain process for the triggering of extreme events. RCs with mode of TB 10.4 at 230–265 K. Despite the low cloud top, these RCs contributed around 39.8% of the total rainfall amount. This result supported that many extreme precipitation events are produced by relatively weak convective systems (Xu et al ., 2022). RCs with mode of TB 10.4 at 230–265 K were related to the quasi‐stationary front over south China; therefore, they were distributed near the average location of front at 23°–27°N.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al. (2022) have also found that convection with limited ice contents can equally bring heavy rainfall. Moreover, Dolan et al.…”
Section: Introductionmentioning
confidence: 96%
“…First, Hamada et al (2015) have obtained the weak linkage between the heaviest rainfall and tallest convective storms. Xu et al (2022) have also found that convection with limited ice contents can equally bring heavy rainfall. Moreover, Dolan et al (2018) have identified two distinct DSD types both causing heavy rainfall from global observations, which are characterized by relatively larger (smaller) raindrop mean size and lower (higher) number concentration, and correspond to the warm-rain (ice-based) convection.…”
mentioning
confidence: 94%
“…Xu et al. (2022) reported an equal contribution (30%) from intense and weak convection over tropical and subtropical land based on the space‐borne PR observations. Huang et al.…”
Section: Introductionmentioning
confidence: 99%